This Pengaruh Return On Asset dan Leverage terhadap Tax Avoidance dengan Corporate Governance sebagai Variabel Pemoderasi pada Perusahaan Properti dan Real Estate di BEI - Adelia Octaviani; Yudha Trishananto (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - This study aims to answer the effect of return on assets (ROA) and leverage on tax avoidance with corporate governance as a moderating variable. Research method - The data used in this research is secondary data, namely data in the form of annual financial reports on property and real estate companies that have been listed on the Indonesia Stock Exchange in 2018-2020. Sampling in this study used a purposive sampling method, namely taking samples according to certain criteria. The data analysis method used was multiple linear regression analysis, using the eviews version 9.0 program. Findings - The results of testing the hypothesis show that ROA has no effect on tax avoidance. Leverage has a positive and significant effect on tax avoidance. Simultaneously ROA and leverage have a positive and significant effect on tax avoidance. Corporate governance can moderate the effect of ROA on tax avoidance. Corporate governance can moderate the influence of leverage on tax avoidance. Implication - The corporate governance variable can strengthen the level of tax avoidance because the data obtained by the researcher describes the independent commissioner as a party who is not bound in any way with the controlling shareholder, has no affiliation with the board of directors or the board of commissioners and does not serve as a director in a company.